ANALISIS INDEKS KONDISI KEUANGAN PEMERINTAH DAERAH PROVINSI ACEH TAHUN 2015-2017 - Yati, Irna Mardi; Asmara, Jhon Andra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The study aims to analyze the region's financial state in aceh within 2015-2017. The financial condition is measured by using indexing measures developed by ritonga (2014), which are made up of six dimensions of short term solvability, long-term solvability, budget solvability, financial flexibility, financial independence, service solvability. In 2015, analysis was developed by augmenting the operational solvability dimension. This study is using qualitative descriptive methods and analysed a secondary data obtained through documentary techniques. The result of this study shows that within 3 years the financial district/city in aceh that got the best category of index value is Sabang (0.488), Banda Aceh (0.452), Aceh Tengah (0.444), Aceh Besar (0.389), and Gayo Lues (0.382). While the area government with the value of the financial conditions of the lowest financial level or ranked category is Aceh Tenggara (0,177), Aceh Singkil (0,148) Lhokseumawe (0,106).